Considerations on Ethics, Law and Environment - Foy Valencia, Pierre (2009)
This essay addresses the importance that environmental ethics is progressively acquiring in relation to the various forms of the contemporary practice of Law, as well as its diversified areas or specialties and, by the way, particularly with respect to Environmental Law. To this end, we will first identify conceptually the scenario and process of environmental ethics as a conditioning presupposition that impacts on the multiple mechanisms of social action -read politics, economy, education, legal systems, among others-. Then, we will establish some premises on the professional responsibility of the lawyer in particular and how these should be integrated in an ethical-environmental perspective or, if you will, based on an ethics of sustainability. Finally, we will interpret how such considerations should be articulated with the practice of legal disciplines, especially with Environmental Law, emphasizing the issue of corruption with environmental concerns.